What about Belem? The question of appropriation of heritage in a parish of Lisbon. - Teixeira-da-Silva, Rafael H. [UNESP] (Revues Org, 2017)
Regardless of whether celebrated or repudiated the past is omnipresent. While the personal traits imbued in these elements will succumb to time, their collective aspects remain endless. What was once a dilettante past presents itself currently as an endless and relentless crusade for heritage, a fact that has immediate consequences on the appropriation of the urban territory. Coupled with the trend of adopting a standardized approach to heritage - patrimonalization - the main subject of this article is in this interlace. For the development of this work, the chosen area of study was the neighborhood of Santa Maria de Belem, located in the western region of the city of Lisbon-Portugal. Endowed with an important architectural ensemble entitled by UNESCO as World Cultural Heritage in 1983, the area comprises two significant monuments, the Monastery of Hieronymites and the Tower of Belem. In order to examine how the phenomenon of patrimonalization reflects itself in the appropriations of Belem, an ethnographic-oriented research was conducted, using qualitative research methods. In this sense, the research is based on semi-structured interviews and participant observation, likely to illustrate the representations of place in Belem and its appropriation by the local population. Through the survey, it was possible to identify the most significant spaces in the neighborhood life of respondents who seek to maintain their traditional customs and practices, while new habits and experiences have been created by the patrimonalization processes and the touristification of the place.
Keywords: Belem; World Heritage; Heritagization; Territorial Appropriation; Sense of belonging